2008
DOI: 10.1016/j.gaitpost.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Should trunk movement or footfall parameters quantify gait asymmetry in chronic stroke patients?

Abstract: The purpose of this study was to investigate gait asymmetry in chronic stroke patients in comparison with subjects with no known asymmetries. Further, we wanted to decide which gait symmetry parameter has the best ability to discriminate between the two groups. Twenty subjects with hemiplegia (mean age 58 years, S.D.=8 years) and 57 subjects with no known gait asymmetry (mean age 77 years, S.D.=5 years) walked six times along a 7-m walkway at slow, preferred and fast speed. Measures of vertical, anteroposterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 24 publications
3
55
0
Order By: Relevance
“…[1][2][3][6][7][8][9][10]12,18 First, we found that asymmetry in neither component was significantly correlated with mean step-length asymmetry, indicating that variations in step-length asymmetry cannot be fully explained by the components of trunk progression (TP) and forward foot placement relative to the trunk (FFP) in isolation. Second, Figure 2 clearly shows that step-length asymmetry is, by and large, the sum of asymmetries in TP and FFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][6][7][8][9][10]12,18 First, we found that asymmetry in neither component was significantly correlated with mean step-length asymmetry, indicating that variations in step-length asymmetry cannot be fully explained by the components of trunk progression (TP) and forward foot placement relative to the trunk (FFP) in isolation. Second, Figure 2 clearly shows that step-length asymmetry is, by and large, the sum of asymmetries in TP and FFP.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 As a result, the trunk does not displace as far forward of the supporting foot during paretic single limb support, resulting in shorter nonparetic than paretic steps ( Figure 1A). Hodt-Billington and colleagues 12 recently concluded, however, that footfall and trunk movements reflect different aspects of hemiplegic gait, implying that asymmetries in trunk progression alone may not fully explain the variations observed in step-length asymmetry. 6,7,13 Another contributor to step-length asymmetry may be differences between paretic and nonparetic forward foot placement relative to the trunk at foot-strike: the farther the nonparetic leg is swung forward with respect to the trunk, the larger the nonparetic step (provided that the trunk is advanced equally far forward during paretic and nonparetic steps; Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…Indication exists that the asymmetries frequently seen in gait parameters poststroke also affect upper-body movements, resulting in asymmetric arm-swing patterns [41]. The hemiparetic gait of patients with stroke is often associated with an adducted arm with no or limited arm swing on the affected side.…”
Section: Wüest Et Al Sensor-based Itug Reliability and Validitymentioning
confidence: 99%
“…Several investigations have been conducted using accelerometers for the quantification of gait [13][14][15][16][17][18][19][20][21][22][23], chair rising [24][25], and balance [20,[25][26][27]. High reproducibility has been found using trunk accelerometry for the measurement of spatiotemporal gait parameters [14][15] and accelerations during gait [15,20].…”
Section: Introductionmentioning
confidence: 99%